Material use in a Low Carbon Energy System - Kakoti, Krishna Kamal; Tasanakul, Worakamon (My University, 2019)
The European Union has, in line with the Paris Agreement, set out ambitious goals to reduce greenhouse gas emissions by the first half of the century. Achieving these goals will require a massive transformation of the European energy system to a low-carbon based system. The large-scale development of low carbon technologies such as solar, wind, hydro, electric vehicles etc. will have an impact on the demand for energy, material and natural resources. This study analyses the steel demand for wind energy and battery electric vehicles within the European Union until 2050 and explores the CO2 emissions associated with steel use. Material flow analysis is used to estimate the steel demand which determines the inflow and the outflow of steel in wind turbines and battery electric vehicle fleet considering their end-of-life. The CO2 emission is quantified based on various scenarios and pathways for the technological development such as HYBRIT (Hydrogen Breakthrough Iron-making Technology) along with EAF (Electric Arc Furnace) in the European steel industry. The findings show that the annual steel demands are within the range of 5 – 26 Million tonnes. Estimates of this demand depend on assumptions of parameters, e.g., the penetration level of the low-carbon technologies, average lifetimes, and material efficiency. With this range of steel demand, the steel requirements for BEV production is 17%-87% of the current steel used in the EU automotive sector. Similarly, the steel required for wind energy is about 34%-44% of the current steel consumed in mechanical engineering in the EU. The additional results show that total cumulative CO2 emissions from steel production for BEV and wind energy would be in the range of 136-382 MtCO2 by 2050 i.e. relatively smaller share (0.004%) of the total EU carbon budget for the period of 2020-2100. The CO2 emissions associated with the steel produced by HYBRIT and EAF for BEV and wind energy could meet the total target level for the EU steel industry in the European Commission strategic long-term vision for a climate-neutral economy by 2050. However, radial measures have to be taken dedicated for the entire EU steel industry to reduce CO2 emissions as emissions associated with entire EU steel production would account for 13% of the EU carbon budget in the year 2050.
Keywords: European Union, Battery electric vehicle, Wind energy, Energy systems,Steel, Material flow analysis, HYBRIT, EAF